Corn Oil-Water Separation Interactions of Proteins and Surfactants at Corn Oil/Water Interfaces - Zhang, Chengcheng (Langmuir : the ACS journal of surfaces and colloids, 2020)
Purification and collection of industrial products from oil-water mixtures are commonly implemented processes. However, the efficiencies of such processes can be severely influenced by the presence of emulsifiers that induce the formation of small oil droplets dispersed in the mixtures. Understanding of this emulsifying effect and its counteractions which occur at the oil/water interface is therefore necessary for the improvement of designs of these processes. In this paper, we investigated the interfacial mechanisms of protein-induced emulsification and the opposing surfactant-induced demulsification related to corn oil refinement. At corn oil/water interfaces, the pH-dependent emulsifying function of zein protein, which is the major storage protein of corn, was elucidated by the surface/interface-sensitive sum frequency generation (SFG) vibrational spectroscopy technique. The effective stabilization of corn oil droplets by zein protein was illustrated and correlated to its ordered amide I group at the oil/water interface. Substantial decrease of this ordering with the addition of three industrial surfactants to corn oil-zein solution mixtures was also observed using SFG, which explains the surfactant-induced destabilization and coalescence of small oil droplets. Surfactant-protein interaction was then demonstrated to be the driving force for the disordering of interfacial proteins, either by disrupting protein layers or partially excluding protein molecules from the interface. The ordered zein proteins at the interface were therefore revealed to be the critical factor for the formation of corn oil-water emulsion